Exposition de la paix - Picasso, Pablo ([Cirque d'Hiver], 1949)
Reproduction of Picasso painting of dove Poster advertising exhibition on peace held at the Cirque d'Hiver, Paris, 24 April-24 May, 1949 PO-0800